The geographical factors affecting ICT diffusion process in the healthcare sector. A case study in Nagasaki Prefecture, Japan - Tsutomu Nakamura (Netcom)
This paper illustrates the diffusion of information and communication technology (ICT) in the healthcare sector, using a case study focusing on a medical information system, namely, Ajisai Net, based in Nagasaki Prefecture, Japan. Regional differences in diffusion patterns and their factors are indicated through a focus on the decision-making of related actors, including system-promoting agencies. This study also clarifies the status of system utilization and the effects of and issues with the system. System utilization spreads through system-promoting agencies in the form of increases in information-disclosure facilities. The diffusion process of this case differed from the hierarchical effect. The city of Omura was the first place where participating facilities could access the system in the infrastructure-building phase, followed by Nagasaki and Kamigoto in the spatial-expansion phase, followed by Sasebo, Isahaya, and Shimabara when widespread dissemination was achieved to the entire prefecture. Based on the ICT’s utilization, the results demonstrate that the diffusion of medical information system was determined by existing social relations ; however, the degree of social relations was not always proportional to the size of the urban area. System-diffusion patterns were found to be a different form than those in previous studies. Nagasaki Prefecture contains many isolated islands and has large internal regional differences in medical resources. In response to these geographical conditions, cooperative relationships among healthcare providers had already been developed before the introduction of ICT. This study suggests that effective use of existing social relationships can establish governance that moves a pattern from competition to coexistence.